Peer Tutor Learning Model in CRE-Based Discipleship Teaching According to Matthew 28: 19-20 at High Schools in Makassar City - Hana, Sarce Rien; Weismann, Ivan Th. J. (Sekolah Tinggi Theologia Jaffray, 2020)
This scientific work digs deeper into the peer tutoring learning model to be applied to Christian Religious Education (CRE) teaching in high schools. The peer tutoring learning model contained the following steps. First, choose the material and divide it into sub-materials. Second, the teacher forms heterogeneous groups of students as many sub-materials. Third, each group learns the material guided by intelligent students. Fourth, allow sufficient time for preparation both inside and outside the classroom. Fifth, each group, through their representatives, submits sub-materials following the given tasks. The teacher remains as a resource. Sixth, provide conclusions and clarifications if there is a student understanding that needs to be straightened. Besides, the problem of achieving CRE goals for students, as well as the material presented in curriculum learning, touches on Matthew 28:19-20's mandate. The formulation of the problem studied is â€œHow is the concept of discipleship, according to Matthew 28:19-20 applied to the teaching of CRE in high schools using the peer tutoring learning model?â€ The aim to be achieved in this research is to formulate disciplinary formulas and materials, and according to Matthew 28:19-20 to be applied by using the model of peer tutoring in teaching CRE at High School in Makassar City. The method used in this study is a research and development method or in English called research and development abbreviated as R&D. The main conclusion reached is CRE-based discipleship teaching according to the Gospel of Matthew 28:19-20 in line with the Great Commission, thereby increasing the chances of the commission being carried out.Tulisan ilmiah ini menjelaskan lebih dalam model pembelajaran tutor sebaya untuk diterapkan pada pengajaran Pendidikan Agama Kristen (PAK) di sekolah menengah. Selain itu, masalah pencapaian tujuan CRE untuk siswa, serta materi yang disajikan dalam pembelajaran kurikulum menyentuh pada Amanat Agung dalam Injil Matius 28: 19-20. Rumusan masalah yang diteliti adalah â€œBagaimana konsep pemuridan menurut Matius 28: 19-20 diterapkan pada pengajaran CRE di sekolah-sekolah tinggi menggunakan model pembelajaran tutor sebaya?â€ Metode yang digunakan dalam penelitian ini adalah metode penelitian dan pengembangan disingkat dengan metode R&D. Hipotesis dalam penelitian ini adalah sebagai berikut: Siswa yang diberikan materi pengajaran PAK sama dengan materi pengajaran Yesus berdasarkan Matius 28: 19-20 menggunakan model pembelajaran Peer Tutor yang mengalami perjumpaan dengan Tuhan Yesus. Siswa kemudian menggunakan bahan yang diajarkan kepadanya untuk memuridkan siswa lain, dan seterusnya sampai semua bangsa menjadi murid-Nya. Kesimpulan utama yang dicapai adalah pengajaran PAK berbasis pemuridan sesuai dengan Injil Matius 28: 19-20 sejalan dengan Amanat Agung, dengan demikian meningkatkan pelaksanaan Amanat Agung.